Case Study of the Consciousness within Scientific Paradigms of Psychology, Philosophy and Linguistics - O V Kazachenko (RUDN Journal of Language Studies, Semiotics and Semantics, 2015)
The article considers the topic of consciousness and the evolution of views in various branches of science. The author gives a definition of “consciousness” and is trying to find a common problem field of this concept in other disciplines. There is a review of Russian and foreign literature on the study of this issue. The article outlines research fields in which consciousness is being conducted. The article explores the main concepts associated with consciousness, such as language, consciousness, culture, worldview and society. It discusses the features of consciousness, its ideal and material nature, structure, components and its links to human activity. The article focuses on the problem of consciousness emerging and evolving through language.